2018
DOI: 10.14395/hititilahiyat.488670
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitatıve Research on Mixed or Single Sex Based Education in Higher Religious Education

Abstract: İlahiyat fakültelerinde verilen eğitimin karma olması, zaman zaman tartışmalara sebep olan bir konudur. Son yıllarda özellikle öğrencilerin yürüttüğü kampanyaların neticesinde, bu konu tekrar tartışmaya açılmıştır. Bunun neticesinde bazı İlahiyat fakültelerinde karma eğitim uygulamasına son verilirken, bazı fakültelerde ise itirazlara rağmen karma eğitim uygulaması devam etmektedir. Karma eğitim tartışmaları bilimsel yaklaşım yerine rasyonel argümanları gölgeleyen politik/ideolojik karşıtlıklar üzerinden ve ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The transition from single-gender education to mixed-gender education has been a difficult process in Turkey; however, limited number of studies has been conducted on the effects of this change. When these studies are examined in general, theoretical studies in which thoughts and historical process on mixed and single-gender education were discussed (Kamer, 2013;Kamer, 2017;Ulaş, 2012) and two qualitative studies (Altıntaş, 2018;Coşkun, 2018) on mixed-gender education have been conducted. A study conducted in Turkey by Erarslan and Rankin (2013) showed that students who attended single-gender education schools have more egalitarian attitudes about roles in family life when compared with students who attended mixed -gender education schools.…”
Section: Introductionmentioning
confidence: 99%
“…The transition from single-gender education to mixed-gender education has been a difficult process in Turkey; however, limited number of studies has been conducted on the effects of this change. When these studies are examined in general, theoretical studies in which thoughts and historical process on mixed and single-gender education were discussed (Kamer, 2013;Kamer, 2017;Ulaş, 2012) and two qualitative studies (Altıntaş, 2018;Coşkun, 2018) on mixed-gender education have been conducted. A study conducted in Turkey by Erarslan and Rankin (2013) showed that students who attended single-gender education schools have more egalitarian attitudes about roles in family life when compared with students who attended mixed -gender education schools.…”
Section: Introductionmentioning
confidence: 99%